If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 19 + -2y + -1(6 + -4)(7y + -2) + 3y + 15 = 0 Combine like terms: 6 + -4 = 2 19 + -2y + -1(2)(7y + -2) + 3y + 15 = 0 Reorder the terms: 19 + -2y + -1 * 2(-2 + 7y) + 3y + 15 = 0 Multiply -1 * 2 19 + -2y + -2(-2 + 7y) + 3y + 15 = 0 19 + -2y + (-2 * -2 + 7y * -2) + 3y + 15 = 0 19 + -2y + (4 + -14y) + 3y + 15 = 0 Reorder the terms: 19 + 4 + 15 + -2y + -14y + 3y = 0 Combine like terms: 19 + 4 = 23 23 + 15 + -2y + -14y + 3y = 0 Combine like terms: 23 + 15 = 38 38 + -2y + -14y + 3y = 0 Combine like terms: -2y + -14y = -16y 38 + -16y + 3y = 0 Combine like terms: -16y + 3y = -13y 38 + -13y = 0 Solving 38 + -13y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-38' to each side of the equation. 38 + -38 + -13y = 0 + -38 Combine like terms: 38 + -38 = 0 0 + -13y = 0 + -38 -13y = 0 + -38 Combine like terms: 0 + -38 = -38 -13y = -38 Divide each side by '-13'. y = 2.923076923 Simplifying y = 2.923076923
| X^2-5x-14*x-5=0 | | 21=8y-4 | | .4=16 | | c=2.2t^2-66t+655 | | .4=15 | | 2.1+10y=-7.9 | | 2(x-1)+6x=14 | | M^2=-m+20 | | x^2+y^2-10y-39=0 | | 6y+4x=-32 | | 4x+10=6x+14 | | (x-2)2+8=12 | | Y^2=15y-50 | | 3m+2+m+6+7m-16+3m=360 | | 4(4x+3)=60 | | 10-3x=4-2x | | Y^2=-9y-8 | | 4x^4-73X^3+28x^2+24x-45=0 | | 9x-2=-2(2x+4)-3(2x-2) | | a^2+11a-22=0 | | -16+5x=7(-6+8x)+3 | | 0=-16t^2+40t+2 | | (3i)(-2+6i)= | | 1x+.56=-.67 | | 5(x+3)+5=10 | | 52y=78 | | 4a+3=16 | | -0.7(0.3x-0.3)=-4.48 | | -72=-8y+12+4y-16 | | 3X+11+8=-6X+11+62 | | 2n+7=-19 | | Y^2+35=-12y |